2018
DOI: 10.1002/app.46928
|View full text |Cite
|
Sign up to set email alerts
|

New composite membrane poly(vinyl alcohol)/graphene oxide for direct ethanol–proton exchange membrane fuel cell

Abstract: This study investigated a simple synthesis of a crosslinked poly(vinyl alcohol)/ graphene oxide composite membrane with lower ethanol permeability membrane for passive direct ethanol-proton exchange membrane fuel cells (DE-PEMFCs). The chemical and physical structure, morphologies, ethanol uptake and permeability, ion exchange capacities, water uptake, and proton conductivities were determined and found that transport properties of the membrane were affected by the GO loading. The composite membrane with optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 59 publications
(118 reference statements)
2
44
0
Order By: Relevance
“…Moreover, the modern lifestyle is extremely dependent on an electronic device, mobile, household appliance, and portable power generation; lifestyle that will be expecting the demand for electricity will increase further to 44% from 2006 to 2030. 10,11 Conventionally, fuel cells are divided to lower temperature fuel cells (<250°C ) 12 such as polymer electrolyte membrane fuel cell (PEMFC), 13 direct alcohol fuel cell, 14 and hightemperature fuel cells (400-1000°C) 15 such as molten carbonate fuel cell 16 and solid oxide fuel cell. 4,5 Fuel cell technologies are one of promising energy production to meet the needs of the world's energy demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the modern lifestyle is extremely dependent on an electronic device, mobile, household appliance, and portable power generation; lifestyle that will be expecting the demand for electricity will increase further to 44% from 2006 to 2030. 10,11 Conventionally, fuel cells are divided to lower temperature fuel cells (<250°C ) 12 such as polymer electrolyte membrane fuel cell (PEMFC), 13 direct alcohol fuel cell, 14 and hightemperature fuel cells (400-1000°C) 15 such as molten carbonate fuel cell 16 and solid oxide fuel cell. 4,5 Fuel cell technologies are one of promising energy production to meet the needs of the world's energy demand.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 There are various types of fuel cell classified based on operating temperature, types of electrolyte, fuel consumption, etc. 10,11 Conventionally, fuel cells are divided to lower temperature fuel cells (<250°C ) 12 such as polymer electrolyte membrane fuel cell (PEMFC), 13 direct alcohol fuel cell, 14 and hightemperature fuel cells (400-1000°C) 15 such as molten carbonate fuel cell 16 and solid oxide fuel cell. 17 Solid Oxide Fuel Cells (SOFCs) are an electrochemical energy conversion device contracted with solid dense electrolyte and sandwich with two of the porous electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…A low activation energy indicated that there were more than one mechanism involved in ionic transfer inside electrolyte membrane including hopping mechanism through the quaternary ammonium group grafted in polymer matrix and vehicular mechanism in KOH dopant and GA inside the free volume. The lower energy barrier has result in the lower activation energy …”
Section: Resultsmentioning
confidence: 97%
“…Introduction of the quaternary ammonium group will be beneficial for hopping mechanism. The changes of crystallinity structure to amorphous was contributed to enhance the anion mobility of hydroxyl ion because the native structural relaxation and segmental motions of the matrix PVA makes it easier to ion transport diffusion . Hence, the amorphous structure has enhance the ionic conductivity performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation